Sosialisasi dan Pendampingan Produksi Telur Asin dari Telur Bebek untuk Meningkatkan Ekonomi Masyarakat di Desa Mekar Baru: Pengabdian - Andriani, Tri; Siregar, Nurul Hikmatul Alawiyah; Optari, Leni Kurnia; Dewantoro, Riy; Pane, Dian Novita Sari; Marpaung, Rispan Kurniawan; Arjuna, Arjuna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity was conducted in Mekar Baru Village, Sei Balai District, Batu Bara Regency, with the aim of improving the community's skills and economic well-being through outreach and mentoring in the production of salted eggs from duck eggs. Methods used included outreach, demonstrations of salted egg production, and assistance in packaging, pricing, and product marketing. The results of the activity showed a significant increase in community understanding of salted egg production techniques, as evidenced by the participants' success in independently practicing the production steps. The resulting product was of good quality, with a firm yolk texture, an even salty flavor, and greater appeal after the packaging improvements. Furthermore, some participants saw an increase in additional income of Rp 200,000–Rp 400,000 per month from the sale of salted eggs. However, the community still faces challenges such as limited capital, simple packaging, and limited market access. Overall, these activities have had a positive impact on community empowerment, opening new business opportunities, and demonstrating the potential of salted eggs as a superior village product with potential for further development.